2022
DOI: 10.1007/s00404-022-06522-3
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian torsion in the pediatric population: predictive factors for ovarian-sparing surgery—an international retrospective multicenter study and a systematic review

Abstract: Study objective Ovarian torsion (OT) in pediatric age is a challenging condition to diagnose and treat. To date, there is still no clear consensus about its management. Our aim was to assess some possible associated factors that can help surgeons in decision-making. Design We conducted a retrospective multicentric study of pediatric OT surgically treated between 2010 and 2020 in six Italian and German institutions, comparing our findings with a literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(123 reference statements)
0
0
0
Order By: Relevance
“…Several studies emphasize the importance of improving the time to diagnose adnexal torsion and its accuracy, utilizing clinical, laboratory, and imaging characteristics [6][7][8]. Rapid diagnosis is essential for successful outcomes, particularly when detorsion, while preserving the ovary, is desired [6]. A recent investigation has revealed that, despite the availability of diagnostic methods, there are instances where this condition goes unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies emphasize the importance of improving the time to diagnose adnexal torsion and its accuracy, utilizing clinical, laboratory, and imaging characteristics [6][7][8]. Rapid diagnosis is essential for successful outcomes, particularly when detorsion, while preserving the ovary, is desired [6]. A recent investigation has revealed that, despite the availability of diagnostic methods, there are instances where this condition goes unnoticed.…”
Section: Introductionmentioning
confidence: 99%